Perlindungan Hak Cipta Terhadap Konten Aplikasi Tiktok yang Disebarluaskan Tanpa Izin - Made Yunanta Hendrayana; Nyoman Putu Budiartha; Diah Gayatri Sudibya (Jurnal Preferensi Hukum, 2021)
Tiktok is a popular application, lots of videos from the Tiktok application are becoming famous. There are people who take advantage by uploading the famous TikTok video on other social media and receiving endorsement for the account. As for the formulation of the problem (I) How are the Copyright protection arrangements for content in the Tiktok application? (2) What is the responsibility of the owner of tiktok content whose content is distributed without the permission of the creator or creator? This journal uses normative legal research methods. The results of the study state that the regulation of copyright protection for content in the Tiktok application is regulated in Law umber 28 of 2014 concerning Copyright and Terms of Service for the Tiktok Application which prohibits someone from distributing and reproducing Tiktok content for commercial purposes. For the accountabi I ity of the owner of tiktok content that is disseminated without permission, namely sanctions for the distribution oftiktok videos according to Article 113 paragraph 3 of the Copyright Law and the tiktok application can demand compensation and stop distribution of tiktok content in accordance with Article 96 paragraph (I) of the Copyright Law